2015
DOI: 10.1089/ars.2014.6004
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Attenuates Noise-Induced Hearing Loss by Reducing Oxidative Stress

Abstract: The results suggest that the lower levels of oxidative stress incurred by TTS-noise exposure induce autophagy, which promotes OHC survival. However, excessive oxidative stress under sPTS-noise conditions overwhelms the beneficial potential of autophagy in OHCs and leads to OHC death and NIHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
145
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(161 citation statements)
references
References 57 publications
15
145
0
1
Order By: Relevance
“…In addition, more HC loss (mainly OHCs) was observed in mutant mice compared to controls two weeks after noise exposure. Consistent with previous reports [4345], our results indicated that OHCs are more vulnerable to noise compared to IHCs. Failed recovery of ABR thresholds in mutant mice may be partially caused by permanent HC loss in the cochlea.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, more HC loss (mainly OHCs) was observed in mutant mice compared to controls two weeks after noise exposure. Consistent with previous reports [4345], our results indicated that OHCs are more vulnerable to noise compared to IHCs. Failed recovery of ABR thresholds in mutant mice may be partially caused by permanent HC loss in the cochlea.…”
Section: Discussionsupporting
confidence: 93%
“…Under normal physiological conditions, 1–2% of molecular oxygen is reduced to superoxide, a free radical that can be converted to less toxic hydrogen peroxide by mitochondrial superoxide dismutase (SOD2) or proceed in a reaction chain to even more detrimental compounds such as the hydroxyl radical. Increased ROS generation in cochlear fluids and tissues, including in OHCs and the stria vascularis, by traumatic noise is well documented and other free radicals in the form of reactive nitrogen species (RNS) derived from nitric oxide (NO) are also present 1517 . ROS may persist for 7–10 days and spread apically from the basal end of the organ of Corti, thus widening the area of damage well after an exposure has been terminated.…”
Section: Molecular Mechanisms Of Neurosensory Damagementioning
confidence: 99%
“…On the other hand, moderate noise exposure increased ROS in OHCs only marginally thus prompting autophagy, a cellular homeostatic response 17 . The autophagy marker LC3 was upregulated in OHCs of CBA/J mice, and the fact that only a TTS but no permanent damage was observed, suggested autophagy as a protective mechanism against NIHL.…”
Section: Molecular Mechanisms Of Neurosensory Damagementioning
confidence: 99%
See 1 more Smart Citation
“…SIRT1 inactivates p53 and subsequently inhibits p53-mediated apoptosis induced by ROS through deacetylation of p53 [Luo et al, 2001;Vaziri et al, 2001]. Because ROS are well known as major contributors to NIHL [Henderson et al, 2006;Yuan et al, 2015], SIRT1 should be considered a potential target for treatment of NIHL and protection of cochlear hair cells. Moreover, our previous studies demonstrated that SIRT1 is abundantly expressed in the cochlea and downregulated with aging, which is correlated with activation of cochlear p53, cochlear hair cell loss, and age-related hearing loss [Xiong et al, 2014[Xiong et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%